Застосування технологій якості обслуговування в комунікаційних мережах - Demchinsky, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The goal of the article is the development and analysis of the flow control algorithm in the QoS networks. The classification, traffic shaping and queuing algorithms are under scope of the research. Since the usage of ATM technology is the main transport for IP traffic, the transit QoS issues are involved. Additionally, the similarity of IP and ATM QoS and the usage of DiffService mechanisms in ATM networks are investigated.